Lumbar Endoscopic Microdiscectomy: Where Are We Now? An Updated Literature Review Focused on Clinical Outcome, Complications, and Rate of Recurrence. (24th November 2015) - Anichini, Giulio; Landi, Alessandro; Caporlingua, Federico; Beer-Furlan, André; Brogna, Christian; Delfini, Roberto; Passacantilli, Emiliano
Abstract : Endoscopic disc surgery (EDS) for lumbar spine disc herniation is a well-known but developing field, which is increasingly spreading in the last few years. Rate of recurrence/residual, complications, and outcomes, in comparison with standard microdiscectomy (MD), is still debated and need further data. We performed an extensive review based on the last 6 years of surgical series, systematic reviews, and meta-analyses reported in international, English-written literature. Articles regarding patients treated through endoscopic transforaminal or interlaminar approaches for microdiscectomy (MD) were included in the present review. Papers focused on endoscopic surgery for other spinal diseases were not included. From July 2009 to July 2015, we identified 51 surgical series, 5 systematic reviews, and one meta-analysis reported. In lumbar EDS, rate of complications, length of hospital staying, return to daily activities, and overall patients' satisfaction seem comparable to standard MD. Rate of recurrence/residual seems higher in EDS, although data are nonhomogeneous among different series. Surgical indication and experience of the performing surgeon are crucial factors affecting the outcome. There is growing but still weak evidence that lumbar EDS is a valid and safe alternative to standard open microdiscectomy. Statistically reliable data obtained from randomized controlled trials (better if multicentric) are desirable to further confirm these results.